Photoswitchable Fluorescent Self‐Assembled Metallacycles with High Photostability. Issue 16 (19th February 2021) - Chen, Shangjun; Chen, Lijun; Cai, Yunsong; Zhu, Wei‐Hong
Abstract: In this study, photoswitchable fluorescent supramolecular metallacycles with high fatigue‐resistance have been constructed by coordination‐driven self‐assembly by using bithienylethene with dipyridyl units (BTE ) as a coordination donor and a fluorescent di‐platinum(II) (Pt‐F ) as a coordination acceptor. The photo‐triggered reversible transformation between the ring‐open and ring‐closed form of the metallacycles was confirmed by 1 H NMR, 31 P NMR, and UV/Vis spectroscopy. This unique property enabled a reversible noninvasive "off–on" switching of fluorescence through efficient Förster resonance energy transfer (FRET). Importantly, the metallacycles remained structurally intact after up to 10 photoswitching cycles. The photoresponsive property and exceptional photostability of the metallacycles posit their potential promising application in optical switching, image storage, and super‐resolution microscopy. Abstract : Get the glow : Photoswitchable fluorescent supramolecular metallacycles with high fatigue‐resistance are constructed by coordination‐driven self‐assembly by using bithienylethene with dipyridyl units as a coordination donor and a fluorescent di‐platinum(II) as a coordination acceptor via efficient Förster resonance energy transfer.